ANALISIS RASIO PROFITABILITAS DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PT CAMPINA ICE CREAM INDUSTRY TBK TAHUN 2020–2024 - Saragi, Dame Ria Rananta; Sianipar, Lasma Lenida Rosinta; Samosir, Anita Tresia; Siahaan, Junaidi (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This research aims to assess the financial performance of PT Campina Ice Cream Industry Tbk during the 2020–2024 period using profitability and liquidity ratios. The profitability ratios examined in this study include Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), while the liquidity ratios consist of the Current Ratio and Quick Ratio. A quantitative descriptive approach was applied using financial report data from the company. The findings reveal a notable improvement in profitability from 2021 to 2023, followed by a decline in 2024, indicating reduced efficiency in generating profits. In terms of liquidity, the company exhibited a strong position at the start of the period, but experienced a sharp decrease, particularly in the Quick Ratio, during the final two years—implying potential short-term financial challenges. Overall, the company has shown signs of post-pandemic recovery and growth, although better working capital management is necessary to ensure long-term financial stability.